2014
DOI: 10.1007/s00484-014-0877-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic variability of the heading–flowering stages of single rice in China based on field observations and NDVI estimations

Abstract: Although many studies have indicated the consistent impact of warming on the natural ecosystem (e.g., an early flowering and prolonged growing period), our knowledge of the impacts on agricultural systems is still poorly understood. In this study, spatiotemporal variability of the heading-flowering stages of single rice was detected and compared at three different scales using field-based methods (FBMs) and satellite-based methods (SBMs). The headingflowering stages from 2000 to 2009 with a spatial resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Previous studies have proposed different smoothing methods to reduce the noise of GLASS LAI time series and found that the OFP method varied by studied times, areas and objectives (Zhao et al, 2016;Wang et al, 2018). Three commonly used methods were chosen in the study to smooth the LAI time-series curves, including the double logistic (DL) method, Savitzky-Golay (S-G) filter method and waveletbased filter (WF) method.…”
Section: Chinacropphen1km Lai Smoothing Methodsmentioning
confidence: 99%
“…Previous studies have proposed different smoothing methods to reduce the noise of GLASS LAI time series and found that the OFP method varied by studied times, areas and objectives (Zhao et al, 2016;Wang et al, 2018). Three commonly used methods were chosen in the study to smooth the LAI time-series curves, including the double logistic (DL) method, Savitzky-Golay (S-G) filter method and waveletbased filter (WF) method.…”
Section: Chinacropphen1km Lai Smoothing Methodsmentioning
confidence: 99%
“…In this study, MVC was used to aggregate the original biweekly NDVI series into monthly series. In MATLAB, the moving averaged filter analysis was used to eliminate the abnormal values in time-series NDVI data [60,61]. To reflect the vegetation more appropriately, the NDVI products were averaged over an entire growing season from April to October to obtain the growing-season NDVI, which is usually used to represent the annual NDVI [62].…”
Section: Data Sourcesmentioning
confidence: 99%
“…Several constraints were applied on the smoothed NDVI time series to reduce outliers of phenometrics. A similar strategy was used in other studies on phenology monitoring for different crops [20,24]. The senescence dates calculated with a local threshold of 0.41 had a very close link to the DWD ripeness stage (RMSE within 1-2 weeks).…”
Section: Phenometrics Extractionmentioning
confidence: 95%